National mental health program of India: a review of the history and the current scenario - Khurana, Sarbjeet; Sharma, Shweta (International Journal Of Community Medicine And Public Health, 2016)
Mental health is an important and essential component of Health. India was one of the first few countries in the developing world to formulate a National Mental Health program (NMHP). NMHP was launched in 1982 with very comprehensive objectives. The basic strategy of NMHP was to integrate the basic mental health care with general health services. At the end of five years of initial implementation of NMHP it was observed that although there were some developments but the financial constraints limited its success. The concept of DMHP was introduced in 1996 and various changes were made in the consecutive five year plans.  In the XIth plan there was an effort to address the main barrier in the mental health service provisions i.e. the shortage of manpower. The NMHP in the XIIth plan has a focus on psychiatric problems specific to vulnerable sections of the population. The program has had various modifications since the time of its inception and now that the time is approaching for the XIIth plan to conclude it would be an opportunity to have deliberations over the success and the failures of the program and to take the program to the next level.